A common currency for Pacific island countries: A revisit - T.K., Jayaraman; Choong, Chee-Keong (2007)
This paper re-visits the topic of a common currency for the Pacific region, comprising 14 Pacific island countries (PICs) and the region’s two advanced countries, Australia and New Zealand. The PICs are highly dependent upon Australia and New Zealand for trade in goods and services and aid inflows. Earlier studies on regional common currency, which dealt with certain aspects of the optimum currency area conditions, took into consideration three kinds of shocks, namely shocks in world output, domestic output and price levels. Since PICs’ growth is influenced by regional developments to a larger degree than by world developments, this paper takes into consideration regional shocks, in addition to shocks in global and national outputs. Using variance decomposition analysis in this paper we investigate whether PICs and the region’s two advanced countries could be suitable candidates for a currency union.